Simple and reversible method to control the surface energy of ITO branched nanowires for tuning wettability of micro/nanoscale droplets - Cho, Won Seok; Park, Jae Yong; Yu, Hak Ki; Dong, Wan Jae; Lee, Jong Lam (Applied Surface Science, 2025)
Reversible control of hydrophobic and hydrophilic surfaces has gained attention due to their potential applications in microfluidic devices, membranes for electrochemical cells, and sensors. While external stimuli such as temperature and electric field can regulate surface properties, they cannot be selectively applied to specific regions, which limits the patterning of areas with different surface energies. Here, we present a simple and reversible method for converting hydrophobic and hydrophilic properties through surface treatments involving nonpolar (−CFx) or polar groups (–OH) on indium tin oxide branched nanowires (ITO BRs). The formation of nonpolar groups results in superhydrophobic surface. Subsequent ultraviolet ozone treatment, using a shadow mask, induces the exposed area to transition into a superhydrophilic state, while the unexposed area retains superhydrophobicity. This demonstrates the potential for selective-area surface energy patterning. Furthermore, we investigate the wetting behavior of nanoscale Ag nanoparticles (NPs) on surface-modified ITO BRs. It is observed that size and shape of Ag NPs depend on the surface energy of ITO BRs. Consequently, controlling the surface energy leads to the formation of unique geometric structure of Ag NPs, enhancing plasmonic light absorption and scattering at specific resonant wavelengths.
Keywords: Branched nanowires; Energy; Hydrophilic surfaces; Hydrophobic and hydrophilic; Hydrophobic surfaces; Nanoscale droplets; Reversible control; Simple++; Surface-plasmon; Transparent electrode; Surface energy; Surface plasmon; Transparent electrode; Wetting